2014
DOI: 10.1007/s12182-014-0313-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic pattern of belt-wide petroliferous phenomenon in the eastern Pearl River Mouth Basin and its practical application

Abstract: The Pearl River Mouth Basin (PRMB) covers an area of approximately 20×10 4 km 2. However, oil-gas fields detected in this area thus far are highly concentrated and controlled predominantly by second-order structural belts, the seven largest of which aggregate proved oil reserves of 7.7×10 8 m 3 , accounting for 86% of the total discovered reserve in the basin. These second-order structures have one common phenomenon: oil is contained in all traps present in them. In other words, they are all belt-wide petrolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…For the two main source rocks (Wenchang Formation and Enping Formation), the generation and migration period started in 16-10 Ma and the subsequent peak expulsion period was reached gradually (at 10-5 Ma). The structure of the study area tended to be stable after the Dongsha movement (about 10 Ma), which was favorable for petroleum accumulation and preservation (Shi et al 2014). Therefore, the oil distribution pattern should not be affected by biodegradation or later tectonic movement.…”
Section: Oil Propertiesmentioning
confidence: 96%
See 2 more Smart Citations
“…For the two main source rocks (Wenchang Formation and Enping Formation), the generation and migration period started in 16-10 Ma and the subsequent peak expulsion period was reached gradually (at 10-5 Ma). The structure of the study area tended to be stable after the Dongsha movement (about 10 Ma), which was favorable for petroleum accumulation and preservation (Shi et al 2014). Therefore, the oil distribution pattern should not be affected by biodegradation or later tectonic movement.…”
Section: Oil Propertiesmentioning
confidence: 96%
“…Recent exploration has indicated that the geological reserves of hydrocarbons in the Huixi half-graben amount to 22.09 × 10 8 t, accounting for 34.3% of the Pearl River Mouth Basin reserves. More than 50% of the Huixi reserves are in the Zhujiang Formation (Shi 2013;Shi et al 2014). This finding further supports the Huixi half-graben being a major hydrocarbon-rich area in the Pearl River Mouth Basin.…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation